The diversity in holy basil (Ocimum tenuiflorum) germplasm from India - MALAV, PAVAN KUMAR; PANDEY, ANJULA; GUPTA, VEENA; KUMAR, ASHOK; BHATT, K C; RAINA, ARCHANA; AKHTAR, JAMEEL; GAIKWAD, AMBIKA; AHLAWAT, OMBIR SINGH; DHAKA, RAJKUMAR (The Indian Journal of Agricultural Sciences, 2020)
A total of one hundred and nine accessions of cultivated holy basil (Ocimum tenuiflorum L.) germplasm, representing different phyto-geographical regions of India were investigated for morphological characterization. Data were recorded on 32 descriptor traits (both qualitative and quantitative) using the minimal descriptors developed by the ICAR-National Bureau of Plant Genetic Resources, with minor modifications. Analysis of the data was carried out using Ward’s Minimum Variance method and categorized into seven major clusters. PCA analysis revealed that the first six principal components (Eigen value greater than 1), are contributing 72.33% of the total variance which were mostly influenced by mature leaf length, leaf width, leaf petiole length, plant height, seed length, seed width, days to flower initiation, essential oil percentage, seed length/width ratio, leaf length/width ratio, number of primary branches and fresh herbage yield. All the accessions showed high degree of variation, indicating rich morphological diversity within the population.